The effects of progesterone therapy in pregnancy: vaginal and intramuscular administration. (3rd July 2021) - Hantoushzadeh, Sedigheh; Sheikh, Mahdi; Shariat, Mamak; Mansouri, Roodabeh; Ghamari, Azin; Golshahi, Fatemeh
Abstract: Aim: This study was performed to evaluate the effects of vaginal versus intramuscular progesterone supplementations on the mood, quality of life, and metabolic changes in pregnant women with the history of previous preterm birth. Methods: This study was conducted as a prospective, randomized, open label, clinical trial evaluated 100 pregnant women who referred for prenatal visit, with 16–17 weeks of gestation from September 2014 through October 2015. The mothers were then randomly allocated into two groups: the vaginal progesterone group to receive 400 mg cyclogest vaginal suppositories (Actavis, UK limited, England) once daily, and the intramuscular progesterone group to receive weekly intramuscular injections of 250 mg of 17-hydroxyprogesterone caproate (17-HPC) (Bayer Schering Pharma, Germany), starting from the 16th to the 35th weeks of pregnancy. Demographics, medical and obstetrical history, sleeping disturbances, alteration in sexual desire, nausea/vomiting, serum levels of fasting blood sugar (FBS), high-density lipoprotein (HDL), and low-density lipoprotein (LDL) were evaluated, first and 8 weeks later. Results: About 11 (11.2%) screened positive for psychosocial disorders; 25 (25.5%) had sleep disturbance, 11 (11.2%) had alteration in sexual desire, and 29 (29.6%) had nausea/vomiting upon enrollment. After 2 months of receiving daily vaginal progesterone, there was a significant increase in the GHQ-28 score ( p  < .001), and rates of positive screening for psychosocial disorders ( p  = .001) in this group. No statistically significant differences were observed in the HDL levels ( p  = .06), LDL levels ( p  = .15), rates of impaired FBS ( p  = .08), nausea/vomiting ( p  = .2), sexual desire alteration ( p  = .56), and sleep disturbance ( p  = 1) in the participants who were randomized to this group. Conclusion: Our results indicated that psychosocial disorders increased significantly at 24th week gestational age after 2 months of progesterone consumption in both groups which could show psychological impact of progesterone regardless of the route of consumption. This calls for higher psychological attention in these women.